A Study of the Production and Marketing of Vegetables in the Tripoli Area (LAR) - SUWANI, MUSTAFA; NAWAS, FARID; CHAUDHRY, SHARIF (The Libyan Journal of Agriculture, 2023)
This study was conducted in the latter part of 1973 to identify and find out feasible solutions for the major production and marketing problems facing vegetable growers in the Tripoli area. One-hundred and ten farmers from Ben-Gashier, Al-Azizieh, Tajoura, and Azzahra areas around Tripoli were interviewed personally and asked to fill out a questionnaire concerning the various objectives of the study. It was found out that all sampled farmers grew vegetables. However, different farmers allocated different areas to the production of vegetables. Tomatoes were the most profitable crop due to the existence of a processing industry and a fixed price for tomatoes by the government. The study also revealed that most farmers got their vegetable seeds from abroad and that they were not keeping any farm account records. Thalatha wholesale market in Tripoli was the main marketing outlet for the great majority of the farmers. Besides, it was found out that grading, cleaning and packaging of vegetables before marketing them have an increasing effect on the prices received by the farmers. Nevertheless, farmers expressed concern about the low fixed prices for their crops and were in favor of competitive prices to be determined by the forces of supply and demand.